Combination of Intravesical Chemotherapy and Bacillus Calmette–Guerin Versus Bacillus Calmette–Guerin Monotherapy in Intermediate- and High-risk Nonmuscle Invasive Bladder Cancer: A Systematic Review and Meta-analysis. Issue 3 (January 2016) - Cui, Jianfeng; Wang, Wenbo; Chen, Shouzhen; Chen, Pengxiang; Yang, Yue; Guo, Yunliang; Zhu, Yaofeng; Chen, Fan; Shi, Benkang
Abstract : Abstract: Urothelial carcinoma of the bladder has become a major cause of morbidity, mortality, and health-related costs. There is still no standard instillation therapy against bladder cancer. A meta-analysis was conducted to evaluate the efficacy and toxicity of adding chemotherapy to Bacillus Calmette–Guerin (BCG) in intermediate- and high-risk nonmuscle invasive bladder cancer (NMIBC). All randomized controlled trials (RCTs) that evaluated the efficacy of combination therapy and BCG monotherapy for intermediate- and high-risk NMIBC were comprehensively searched. Relevant databases, including PubMed, Embase, Cochrane Central Register of Controlled trials databases, and American Society of Clinical Oncology (http://www.asco.org/ASCO ), the clinical trial registration website (ClinicalTrials.gov), and relevant trials from the references of selected studies were searched from initial state up to June 6, 2015. Random-effects model was used to estimate hazard ratios (HRs) statistics. All statistical analyses were performed by STATA (version 13.0, College Station, TX). Seven studies, including 1373 patients with intermediate- and high-risk NMIBC, were identified. For disease-free survival, the pooled HRs from all studies was 0.69 (95% confidence interval [CI], 0.48–1.00; P  = 0.048). The disease-free survival benefit was more apparent among patients with intermediate-risk NMIBC ( P  = 0.002) or Ta/T1 with/without carcinoma in situ ( P  < 0.01). In subgroup analysis, a significant reduction in recurrence was found in studies that explored the influence of a perioperative single dose instillation compared with delayed BCG monotherapy (HR = 0.60; 95% CI, 0.38–0.92; P  = 0.021). No significant difference was found for progression-free survival (HR = 0.78; 95% CI, 0.43–1.44; P  = 0.435). Patients with intermediate- and high-risk NMIBC who underwent combination therapy achieved lower rates of recurrence than those who underwent BCG therapy alone. No difference in progression-free survival was found between the 2 different therapy schedules. Better efficacy for a perioperative single dose instillation compared with delayed BCG monotherapy was found in this meta-analysis.